Dinamisasi Politik Identitas di Indonesia (Studi Kasus: Mobilisasi Gerakan 212 Pada Pilkada DKI 2017) - Muhamad Ali Vardan Aminudin; Mutiara Ayudia Pratiwi; Angelica Maria Diahlaksmita Cahyowirawan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
A fairly large mass mobilisation movement had occurred before and during the 2017 DKI elections. The movement arose due to the statement of the former Governor of Jakarta at that time Ahok who was considered to degrade the dignity of Muslims through his statement on the letter Al-maidah which was named the 212 movement. Related to this, this research will analyse the dynamics of identity politics in Indonesia, especially in the case of the mobilisation of the 212 Movement during the 2017 DKI Jakarta Governor Election. The method used in this research is a qualitative approach with a descriptive analysis method to explain or describe a phenomenon. In this research, the main object is the Dynamics of Identity Politics in Indonesia through the Mobilisation Case of the 212 Movement in the 2017 DKI Jakarta Gubernatorial Election while the subjects are the groups involved in the mobilisation process, especially Muslims and religious or political elites who lead the 212 Movement. This research found that there are factors that influence the mobilisation of the 212 masses such as social, political and cultural factors. In addition, there are also findings that religion can be the main construction in the movement.